THE MAJOR CULTURAL DIFFERENCES AND SIMILARITIES IN FORMS OF ADDRESS IN ENSURING POLITENESS DURING COMMUNICATION IN ENGLISH AND UZBEK LANGUAGES - Salomov Narzulla Soyibovich (International Journal of Literature and Language Studies, 2026)
The article provides a comparative study of the principle of politeness in address forms between Uzbek and English languages. This research has been conducted in accordance with P Brown and S.Levinson`s “face saving acts ” and G.Leech`s politeness Maxims . The article also analyzes address terms, illustrating their manifestation in formal, informal situations from lexical-semantic and linguopragmatic points of view. The study takes a deeper look at key major sociopragmatic factors, such as age, gender, social status, and social distance in selecting address forms. The findings reveal that while English address terms expose minimal social status differentiation, in Uzbek culture, address systems rely mainly on the active use of relationship terms and honorific conventions.